Association Between Thrombus Density and Reperfusion Outcomes Using Different Thrombectomy Strategies: A Single-Center Study and Meta-Analysis - Ye, Gengfan; Cao, Ruoyao; Lu, Jun; Qi, Peng; Chen, Juan; Wang, Daming (Frontiers in Neurology, 2019)
Background: For patients with acute ischemic stroke (AIS), the thrombus density on non-enhanced CT (NECT) indicates the composition of the thrombus, a characteristic which impacts the efficacy of mechanical thrombectomy (MT). A previous meta-analysis suggested a correlation between higher thrombus density and successful reperfusion, but some new studies have drawn different conclusions. This single-center study and meta-analysis aimed to detect the association between thrombus density and reperfusion outcomes based on various thrombectomy strategies. Methods: We reviewed anterior circulation AIS patients who underwent MT at our center between July 2015 and May 2019. Thrombus density was recorded as mean Hounsfield Unit (HU) value on 1-mm reconstructed NECT and expanded Thrombolysis In Cerebral Infarction (eTICI) scale was used to evaluate the reperfusion grade. The difference in thrombus density was examined according to reperfusion outcomes. Then, we systematically searched relevant literature on this issue. The random effect model was used to calculate standardized mean difference (SMD), and subgroup analysis was conducted according to MT strategies employed, including stent retriever (SR), contact aspiration (CA), Solumbra (a combination of SR and aspiration) and multiple thrombectomy modalities. Results: Sixty-four patients with anterior circulation AIS were included in our single-center study with 57 (89.1%) achieving successful reperfusion (eTICI2b-3). Retrospective analysis showed no significant difference in thrombus density between eTICI2b-3 and eTICI0-2a reperfusion (65.27 vs. 62.19, p=0.462). As for systematic review, eleven studies were included in qualitative analysis, among which six had data available for meta-analysis. Pooled result showed a comparable thrombus density between eTICI2b-3 and eTICI0-2a reperfusion (SMD 0.14, 95%CI -0.28 to 0.57, p=0.50). Interestingly, in SR subgroup, eTICI2b-3 reperfusion showed a significant higher thrombus density (SMD 0.53, 95%CI 0.10 to 0.96, p=0.02); while an inverse trend was observed in the CA subgroup (SMD -0.48, 95%CI -0.88 to -0.07, p=0.02). Conclusions: Although our meta-analysis did not show a significant association between thrombus density and successful reperfusion, subgroup analysis implicated that SR technique might be prone to retrieve high-density thrombus while the CA subgroup showed an opposite tendency. Further studies are needed to confirm these results and to investigate its role in the optimization of thrombectomy strategy.